Epstein-Barr Virus Limits the Accumulation of IPO7, an Essential Gene Product - Yang, Ya-Chun; Sugden, Bill (Frontiers in Microbiology, 2021)
Epstein-Barr virus encodes more than 40 miRNAs that target cellular mRNAs to aid its infection, replication, and maintenance in individual cells and in its human host. IPO7, also termed Imp7 or RanBPM7, is a nucleocytoplasmic transport protein that has been frequently identified as a target for two of these viral miRNAs. How the viral life cycle might benefit from regulating IPO7 has been unclear, though. We demonstrate with CRISPR-Cas9 mutagenesis that IPO7 is essential in at least three cells lines and that increasing its levels of expression inhibits growth of infected cells. Epstein-Barr virus thus regulates the level of IPO7 to limit its accumulation consistent with its being required for survival of its host cell.